دراسة إحصائية راجعة للجزر المثاني ـ الحالبي في مشفى الأسد الجامعي باللاذقية بين عامي 2007-2002 - كنعان, محمد; ناصر, حسان; محمد, ماهر (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسـة 113 مريضاً راجعوا مشفى الأسد الجامعي باللاذقيـة بشكوى أخماج بولية متكررة فـي الـفترة الـواقعـة بـين عـامـي (2007-2002)، وبعد إجراء الاستقصاءات اللازمة تم تشخيص جزر مثاني حالبي لدى 32 مريضاً منهم، تنقسم إلى 9 حالات عند الذكور مقابل 23 حالة عند الإناث تركزت 15 إصابة مابين عمري (10 - 4) سنوات أظهر فحص البول لدى كل المرضى بيلة قيحية وكان الزرع ايجابياً عند 30 مريضاً وسلبياً عند مريضين وكانت أكثر الموجودات الشعاعية تواتراً على التصوير الظليل للجهاز البولي هي الموجودات التي تدل على التهاب حويضة وكلية مزمن (20 مريضاً ) وأُجري لكل المرضى تصوير مثانة بالطريق الراجع مع أخذ صورة بعد التبول وكانت الدرجات (III - IV) هي الأكثر تواتراً بين درجات الجزر، عالجنا 7 مرضى علاجاً طبياً محافظاً كما عالجنا 25 مريضاً بالجراحة. تابعنا المرضى المُعالجين بإجراء مايلي: - فحص بول شهري ولمدة 6 أشهر - تصوير مثانة بالطريق الراجع بعد (6 -4) أشهر - تصوير بولي ظليل IVP بعد (12 – 6) شهراً. The study includes 113 patients between 2002 and 2007 who came to Al-Assad University Hospital with recurrent urinary tract infections. After investigations, Vesico-ureteral reflux (VUR) was diagnosed in 32 patients divided into 9 cases in males & 23 cases in females. The most common age of patients was between 4 and 10 years. Urine exam showed pyuria in all patients & urine culture was positive in 30 patients. The most common radiological findings in IVP referred to chronic pyelonephritis (20 patients), retrograde cystography was done in all patients and showed that the most common degrees of reflux were (III –IV). 7 patients were treated with conservative therapy. 25 patients were treated with surgical therapy (ureteral reimpantation). Follow-up was through urine exam monthly for 6 months, retrograde cystography after (4-6) months, and IVP after (6-12) months.